Field guards in Hungary - Christián, László (Varstvoslovje, 2021)
Purpose: The purpose of the paper is to illustrate the history, basic rules, activities and the present role of the second most important local governmental law enforcement organisation in Hungary, the field guard services. The paper also aims to place the Hungarian field guard services in an international context, comparing it with the French field guard services. Design/Methods/Approach: The findings of an interview survey and a questionnaire survey on the Hungarian field guard services are presented in the paper with the results of secondary research on the history of the field guard services, their current legislative framework and the activities of the field guard services in France. Findings: Municipalities in Hungary have played a significant role in the maintenance of rural security for centuries through the operation of field guards, formerly field police, as a local governmental law enforcement body. The legal framework for the activities of field guards was laid down in the 19th century, was hardly changed in the communist period, and still defines the security tasks of local governments in relation to the outer areas of municipalities. Based on the research, the image of a service-providing local governmental law enforcement organization emerged, whose role is of crucial importance due to the unique funding system among the local governmental law enforcement organizations. Originality/Value: Field guards, although unavoidable actors in rural law enforcement, have not been the subject of research before, and therefore the authors of the paper examined the legal framework and practical tasks of field guards.
Keywords: field guard service; France; Francija; Hungary; local governmental law enforcement; Madžarska; municipal police; občinska policija; organi pregona na lokalni ravni; podeželsko redarstvo